Inverting interpolated receiver functions with surface wave dispersion and gravity: Application to the western U.S. and adjacent Canada and Mexico. Issue 11 (9th June 2015) - Chai, Chengping; Ammon, Charles J.; Maceira, Monica; Herrmann, Robert B.
Abstract: We use P wave receiver functions from the western U.S. and adjacent regions to construct a receiver function wavefield interpolation scheme that helps to equalize the lateral sampling of the receiver functions and the surface wave dispersion and to greatly simplify the receiver functions. Spatial interpolation and smoothing suppress poorly sampled and difficult to interpret back azimuthal variations and allow the extraction of the first‐order features in the receiver function wavefield, including observations from several ray parameter ranges. We combine the interpolated receiver functions with Rayleigh wave dispersion estimates and surface gravity observations to estimate the 3‐D shear wave speed beneath the region. Speed variations in the 3‐D model correlate strongly with expected geologic variations and illuminate broad‐scale features of the western U.S. crust and upper mantle. The model is smooth, self‐consistent, and demonstrates the compatibility of the interpolated receiver functions and dispersion observations. Key Points: Interpolation of receiver function simplifies the complexity in the waveform Interpolated receiver functions are suitable for 3‐D joint inversion study Jointly inverted velocity structures correlate with known tectonic provinces